Analisis Timbulan, Komposisi dan Proyeksi Limbah Baterai di Kecamatan Cipayung, Jakarta Timur - Qisthi, Aulia; Nabila, Anggi (Syntax Literate, 2025)
The increasing use of primary batteries, such as AA, AAA, C, and D types, in household electronic devices has resulted in a substantial amount of battery waste. These batteries contain heavy elements like zinc (Zn) and manganese (Mn), which pose environmental risks if not properly managed. This study aims to analyse the generation and composition of household battery waste based on socioeconomic level in Cipayung, East Jakarta and to project the battery waste generation at broader city level. The results show that the average household battery waste generation is 56.65 grams per household per month, equivalent to 3.25 battery units. The highest battery waste generation was found among higher-income households. The results also show that the majority of household battery waste of AA and AAA batteries, accounting for 95% of the total waste, with the black mass as the primary component in the battery. Furthermore, the study also projected battery waste generation for East Jakarta which is approximately 38.36 tons per year. The high volume of battery waste generation in East Jakarta highlights the importance of developing a well-planned battery waste management at the urban level.